2006
DOI: 10.1111/j.1399-0039.2006.00695.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex family–based study in systemic lupus erythematosus: association between the R620W polymorphism of PTPN22 and the FcγRIIa (CD32A) R131 allele

Abstract: A functional polymorphism in PTPN22, a gene encoding a phosphatase involved in T-cell signaling, has been associated with autoimmunity. We checked for the prevalence of the PTPN22 R620W polymorphism in multiplex families affected with systemic lupus erythematosus (SLE) and other autoimmune diseases. Its association with other polymorphisms in mannose binding lectin (MBL) and FcgammaRIIa (CD32A) genes was also studied. Deoxyribonucleic acid samples were obtained from 233 Spanish individuals who belonged to 21 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Twin and family studies have revealed a genetic contribution to the etiology of the disease. Meanwhile, a number of risk genes, including BLK, Bank-1, TNFSF4, IRF-5, STAT-4, PTPN22, PD-1, CD11b, and CD32A have been identified [1][2][3][4][5][6][7][8][9][10]. In addition, chronic viral infections may induce the disease and participate in its pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Twin and family studies have revealed a genetic contribution to the etiology of the disease. Meanwhile, a number of risk genes, including BLK, Bank-1, TNFSF4, IRF-5, STAT-4, PTPN22, PD-1, CD11b, and CD32A have been identified [1][2][3][4][5][6][7][8][9][10]. In addition, chronic viral infections may induce the disease and participate in its pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The PTPN22 1858T allele has been positively associated with a number of humoral autoimmune diseases including rheumatoid arthritis (12,17), type 1 diabetes (18,19), and systemic lupus erythematosus (20). The presence of a single PTPN22 1858T allele (1858C/1858T, herein referred to as the 1858C/T genotype) is sufficient to confer risk to disease (12,14,17–20). The homozygous 1858T/1858T (1858T/T) genotype is rare, but confers an additional disease risk (16).…”
Section: Introductionmentioning
confidence: 99%
“…This increase in immune system function has been postulated to play a role in the eventual progression to autoimmunity (15,16). The PTPN22 1858T allele has been positively associated with a number of humoral autoimmune diseases including rheumatoid arthritis (12,17), type 1 diabetes (18,19), and systemic lupus erythematosus (20). The presence of a single PTPN22 1858T allele (1858C ⁄ 1858T, herein referred to as the 1858C ⁄ T genotype) is sufficient to confer risk to disease (12,14,(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Genomic DNA was isolated from peripheral blood leucocytes by standard methods. Genotyping of PTPN22*R620W was carried‐out by polymerase chain reaction–restricted fragment length polymorphism assay as previously described (Balada et al. , 2006).…”
Section: Frequency Of the Ptpn22*r620w Snp Genotypes In Spanish Papsmentioning
confidence: 99%